Adsorption of Acid Red 18 (AR18) by Activated Carbon from Poplar Wood- A Kinetic and Equilibrium Study - Reza Shokoohi; Vahid Vatanpoor; Mansuor Zarrabi; Akram Vatani (E-Journal of Chemistry)
Adsorption process by activated carbon is widely used for removal of dyes. Because of economical limits, activated carbon derived from low cost materials seem to be economical. The aim of this work is preparation of activated carbon from poplar wood and investigation of its ability to removal of (AR18) dye. In this work, we prepared the activated carbon by chemical activation method in electric furnace. In addition we have investigated effect of various parameters such as pH, contact time, dye concentration and adsorbent dosage on dye removal. Langmuir and Freundlich isotherm models have been investigated. Pseudo-first order, pseudo-second order and modified pseudo-first order kinetic models have been used for experimental data. The results showed that removal efficiency was increased with increasing of adsorbent dosage, contact time and decreasing of pH, but with increasing of dye concentration, the removal efficiency was decreased. Adsorption isotherm models showed that Langmuir isotherm model was best fitted onto collected data (r2>0.978). In addition, kinetic models showed that sorption of AR18 onto activated carbon prepared from poplar wood follows the pseudo-first order model (r2>0.9758).